THE IMPACT OF THE INSURANCE PRODUCTS SALES ON THE INSURANCE COMPANY VALUE - TKACHENKO, Nataliia; SELIVERSTOVA, Liudmyla (Scientific journal «World of Finance», 2020)
Introduction. TThe issue of combining the value of the insurance company with the development of the insurance business in terms of formation of an effective system for selling insurance products is investigated. Analyzing in this direction are due to the constant concentration of capital and companies in order to create more competitive insurance structures. Critical scientific analysis on the issues of the insurer value and the development of the insurance products sale system allowed to distinguish a number of key generalizations. The aim is to deepen the theoretical and methodological principles of identifying the value of an insurance company, to formulate the advantages and disadvantages of the basic methods of such assessment and to substantiate the sales system impact on the value of the insurance business. Results. It is substantiated that increasing the value of an insurance company is not only aimed at directly generating income from the sale of an insurer, but is an incentive for expanding its business, enhancing the image of an insurance company, attracting investments for development and improving the quality of services offered. The advantages and disadvantages of individual methods of calculating the insurer value are systematized, namely: determination of the net asset value of the company, comparative valuation, discounted cash flow method. The significance of using the method of residual income or residual net income is proved. It is claimed that the system of the insurance products sale is one of the main elements of formation of the insurance company value. The two-sided influence of the sales system on the value of the insurance business has been determined: as an effective mechanism for increasing sales volume and as the influence of individual components of the sales system on the value of the company. Conclusions. Due to the development of the insurance product sales system as a key element of the insurance company’s value formation, its further growth will be ensured.